Development of a chitosan‐modified PLGA nanoparticle vaccine for protection against Escherichia coli K1 caused meningitis in mice - Zhang, Jin; Sun, Hongwu; Gao, Chen; Wang, Ying; Cheng, Xin; Yang, Yun; Gou, Qiang; Lei, Langhuang; Chen, Yanping; Wang, Xingyong; Zou, Quanming; Gu, Jiang (Journal of nanobiotechnology, 2021)
Escherichia coli K1 (E. coli K1) caused neonatal meningitis remains a problem, which rises the urgent need for an effective vaccine. Previously, we rationally designed and produced the recombinant protein OmpAVac (Vo), which elicited protective immunity against E. coli K1 infection. However, Vo has limited stability, which hinders its future industrial application. Chitosan-modified poly (lactic-co-glycolic acid) (PLGA) nanoparticles were prepared and used as carried for the recombinant Vo. And the safety, stability and immunogenicity of Vo delivered by chitosan-modified PLGA nanoparticles were tested in vitro and in a mouse model of bacteremia. We successfully generated chitosan-modified PLGA nanoparticles for the delivery of recombinant Vo (VoNP). In addition, we found that a freeze-drying procedure increases the stability of the VoNPs without changing the shape, size distribution and encapsulation of the Vo protein. Unlike aluminum adjuvant, the nanoparticles that delivered Vo were immunoprotective in mice even after storage for as long as 180 days. We identified an effective strategy to improve the stability of Vo to maintain its immunogenicity, which will contribute to the future development of vaccines against E. coli K1.